2018
DOI: 10.18657/yonveek.441375
|View full text |Cite
|
Sign up to set email alerts
|

Akademik Gelişim Ve Finansal Okuryazarlık Arasındaki İlişkinin Tespiti Üzerine Bir Araştırma

Abstract: Finansal okuryazarlık finansal piyasaları anlayabilme, tasarruf ve tüketim dengesini kurabilme, finansal risk ve çeşitli alternatifler arasından doğru seçimleri yapabilme yeteneği olarak tanımlanabilir. Finansal okuryazarlık; bireylerin kredi kartı kullanımı, emeklilik planları, konut ve bireysel kredi kullanımının hangi zamanlarda avantajlı olduğunu, sigorta gibi faaliyetlerin nasıl işlediğini ve hangilerinin bireylerin çıkarlarına hizmet ettiğini ortaya çıkarır. Kişilerin finansal okuryazarlık düzeyinin yüks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…Financial Literacy (FL) Financial literacy was previously defined as financial knowledge (Hilgert et al, 2003). Increasing financial literacy knowledge allows individuals to change their consumptionsaving balance, contributing to the economy with the savings via proper investment tools; helping individuals to manage issues like tax, insurance, retirement and loan (Durmuşkaya and Kavas, 2018;Lusardi, 2008aLusardi, , 2008b; Pahlevan Sharif and Naghavi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial Literacy (FL) Financial literacy was previously defined as financial knowledge (Hilgert et al, 2003). Increasing financial literacy knowledge allows individuals to change their consumptionsaving balance, contributing to the economy with the savings via proper investment tools; helping individuals to manage issues like tax, insurance, retirement and loan (Durmuşkaya and Kavas, 2018;Lusardi, 2008aLusardi, , 2008b; Pahlevan Sharif and Naghavi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The common difficulties in measuring financial literacy levels differ according to the way the question is asked. In this study, questions were collected from previous studies to determine the financial literacy level (Durmuşkaya and Kavas, 2018). It consists of basic, intermediate, and advanced financial literacy levels of questions relevant to the Turkish Taxation System, investment information, Turkiye's economic situation, motor and traffic insurance information and retirement system.…”
Section: Scalesmentioning
confidence: 99%
“…Chen and Volpe (1998), Atkinson, McKay, Kempson, and Collard (2007), Nicolini, Cude, and Chatterjee (2013), Thapa (2015), Mändmaa (2019), Acaravcı and Bediroğlu (2019), Sezal (2021) and Onat and Yöntem (2022) concluded that the level of financial literacy increases as students' ages increase. In the study conducted by Durmuşkaya and Kavas (2018) with academicians, it was reported that as the age increases, the knowledge of financial literacy increases.…”
Section: The Hypothesis Of "(H2)mentioning
confidence: 99%
“…According to another definition, it is the knowledge, skills, attitudes, and behaviors needed to make effective decisions with financially accurate forecasts and achieve economic prosperity (Atkinson & Messy, 2012). Finally, according to Durmuşkaya and Kavas (2018), financial literacy is the power to read today's economic markets correctly, establish the money balance, and produce different inferences and alternative solutions against the risks that may arise.…”
Section: Introductionmentioning
confidence: 99%
“…Bu şekilde ekonomik sorunlarla oluşabilecek boşanmaların sayısında da azalma görülebilecektir. 16 Bir ülkede finansal okuryazarlık düzeyinin artması, o ülkede uygulanan ekonomik politikalar ile tasarruf düzeyinin ve finansal kurumların hizmet çeşitliliğinin artması gibi pek çok unsuru olumlu etkilemektedir. Bu nedenle de finansal okuryazarlık birçok ülkede, kamu ve özel sektör kuruluşlarının ilgi alanındadır.…”
Section: Introductionunclassified